A least-squares Monte Carlo framework in proxy modeling of life insurance companies - Anne-Sophie Krah; Zoran Nikolić; Ralf Korn (Risks, 2018)
The Solvency II directive asks insurance companies to derive their solvency capital requirement from the full loss distribution over the coming year. While this is in general computationally infeasible in the life insurance business, an application of the Least-Squares Monte Carlo (LSMC) method offers a possibility to overcome this computational challenge. We outline in detail the challenges a life insurer faces, the theoretical basis of the LSMC method and the necessary steps on the way to a reliable proxy modeling in the life insurance business. Further, we illustrate the advantages of the LSMC approach via presenting (slightly disguised) real-world applications.
Keywords: 330; Least-Squares Monte Carlo method; proxy modeling; life insurance; Solvency II